Peran Guru Pendidikan Agama Islam Dalam Meningkatkan Proses Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam Di SMP Swasta Al-Maksum Stabat - Maisyarah Maisyarah; Muhizar Muchtar; Ahmad Fuadi (Khazanah : Journal of Islamic Studies, 2022)
The Role of Islamic Religious Education Teachers in Improving Student Learning Processes in Islamic Religious Education Subjects at Al-Maksum Stabat Private Middle School. Learning and teaching activities in the classroom are expected to be able to shape student personalities, especially personalities to be motivated in participating in learning activities to memorize verses of the Koran so that students will be better able to deal with certain conditions that require the ability to memorize to practice the subject matter they get at school. The presentation of teaching materials should be packaged in an attractive way and the material delivered in an innovative and creative way, so that teaching activities in the field of Islamic Religious Education can run effectively and efficiently. The role of teachers in the field of Islamic Religious Education is very important in improving students' ability to memorize the Koran, namely through an effective and efficient learning and teaching process. What is the role of the teacher in the subject of Islamic Religious Education in class VII of Al-Maksum Stabat Private Middle School? How is the learning process of Islamic Religious Education for class VII students of Al-Maksum Stabat Private Middle School? Is the role of the teacher able to increase the learning process in the subject of Islamic Religious Education in class VII Al-Maksum Stabat Private Middle School?. The conclusions in this study are: The role of professional teachers in the field of Islamic Religious Education can increase the intensity of moral development for class VII students of Al-Maksum Stabat Private Middle School has been fulfilled by the fact that even in carrying out teaching and learning activities online during the covid 19 pandemic. The role of the teacher the field of moral studies is still carried out by conducting active communication with students using online media or Smart Phone device applications.